Blizzard enterprise: kitchen appliances / Muhammad Hishamuddin Ismail... [et al.] - Ismail, Muhammad Hishamuddin; Ahmad Azhar, Muhammad Arif; Abdul Rahman, Muhammad Fadhil Aiman; Hariri, Muhammad Nur Hakim (2017)
Blizzard Enterprise is a start-up kitchen appliances located in Senai, Johor. Blizzard Enterprise expects to catch the interest of a regular customer base with its broad variety of kitchen appliances.